The efficacy, safety and patient satisfaction of platelet-rich plasma and fluid platelet-rich fibrin in chronic wound healing (2017–2025): A systematic review - Zahreh Khodashenas; Hanieh Pourkalhor (Global Wound Care Journal, 2026)
Background: Chronic wounds pose significant clinical challenges due to delayed healing and high complication rates. Platelet-rich plasma (PRP) and fluid platelet-rich fibrin (PRF) are autologous regenerative therapies that release growth factors to promote healing, yet evidence remains heterogeneous. Aim: This systematic review evaluates the efficacy, safety and patient-reported outcomes of PRF and PRP in chronic wound healing. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, Embase and Cochrane Library (January 2017–March 30, 2025) following PRISMA 2020 guidelines. Eligible studies were randomised controlled trials (RCTs) and clinical trials on PRP/fluid PRF in chronic wounds. Two reviewers independently screened studies, extracted data and assessed risk of bias using Cochrane tools. No meta-analysis was performed due to high heterogeneity. Results: Twenty studies were included for qualitative synthesis. PRP and fluid PRF demonstrated improved wound closure rates, reduced healing time and low adverse events compared to conventional care in diabetic, pressure and surgical wounds. Fluid PRF showed advantages in granulation and angiogenesis, while PRP gel reduced infection and pain. Most studies had moderate risk of bias, mainly due to lack of blinding. Conclusion: PRP and fluid PRF appear safe and effective as adjunct therapies for chronic wounds, particularly in refractory cases. Standardisation of preparation protocols and larger RCTs are needed to confirm long-term benefits.